1993
DOI: 10.1084/jem.178.5.1725
|View full text |Cite
|
Sign up to set email alerts
|

Response to influenza infection in mice with a targeted disruption in the interferon gamma gene.

Abstract: Sullrlmal~rInterferon 7 (IFN-3') is a pleiotropic cytokine secreted by T lymphocytes and natural killer (NK) cells and has been noted to be a first line of host defense in the control of viral infections. To examine further the role of this cytokine in the control of viral infections, mice with a targeted mutation in the IFN-7 gene were infected with influenza virus, and the in vivo antibody and ceil-mediated immune response to viral infection were examined. In addition, cell lines and clones were derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
153
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 36 publications
(43 reference statements)
40
153
3
Order By: Relevance
“…5). In agreement with others, we found that IFN-␥ is not required for the generation of cytolytic effector cells during virus infection (30,58,59). Indeed, vaccinia-specific CTL responses were slightly elevated in IFN-␥ Ϫ/Ϫ mice, which may be due to enhanced proliferation of T cells in the absence of IFN-␥ (45,59).…”
Section: Ctl Responses Are Abrogated In Il-12 ϫ/ϫ Mice But Not In Ifnsupporting
confidence: 79%
“…5). In agreement with others, we found that IFN-␥ is not required for the generation of cytolytic effector cells during virus infection (30,58,59). Indeed, vaccinia-specific CTL responses were slightly elevated in IFN-␥ Ϫ/Ϫ mice, which may be due to enhanced proliferation of T cells in the absence of IFN-␥ (45,59).…”
Section: Ctl Responses Are Abrogated In Il-12 ϫ/ϫ Mice But Not In Ifnsupporting
confidence: 79%
“…However, cytotoxic T cell responses in these mice were comparable to wildtype controls. Interestingly, CD4 cell clones isolated from IFN-γ −/− mice and restimulated in vitro could protect against lethal challenge with influenza via a cytolytic mechanism [50]. It has also been demonstrated that virally infected class-I-deficient mice have CD4 cells capable of lysing Sendai or LCMV-infected targets [11], suggesting that CD4 cells can compensate for the lack of IFN-γ or CD8 cells by becoming killers themselves.…”
Section: Cd4 Effector Mechanisms and Protectionmentioning
confidence: 95%
“…Infection of mice with a targeted disruption of the IFN-γ gene demonstrated increases in type 2 cytokine production and increases in influenza-specific IgG1 antibody secretion [50]. However, cytotoxic T cell responses in these mice were comparable to wildtype controls.…”
Section: Cd4 Effector Mechanisms and Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence that IFN-c is ineffectual against influenza A virus [3]. In fact, IFN-c is not necessary for recovery from primary infection with influenza A virus [30]. IFN-a/b and IFN-c pathways do not contribute to the development of immunity to influenza A virus and protection or recovery from influenza A virus infection [31].…”
mentioning
confidence: 99%